2003
DOI: 10.1053/jhep.2003.50457
|View full text |Cite
|
Sign up to set email alerts
|

Ptk2 And Eif3s3 Genes May Be Amplification Targets At 8Q23–Q24 and Are Associated With Large Hepatocellular Carcinomas

Abstract: We investigated 39 primary hepatocellular carcinomas (HCCs) for aberrations in DNA copy number, using comparative genomic hybridization (CGH). Gain of DNA at 8q was common in these tumors; high-level gains, indicative of gene amplification, occurred most frequently at 8q23-q24. Gains of 8q correlated with large (>5 cm) tumor size. To identify targets of the amplification events involving 8q, we determined expression levels of 14 candidate genes within that region in a total of 41 HCCs by means of real-time qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
84
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 40 publications
5
84
0
Order By: Relevance
“…24 The PTK2 gene has also been identified as a target for the amplification event at 8q23-24, and elevated expression of PTK2 is associated with a large tumor size in HCC. 25 Our data revealed that four genes were correlated with poor differentiation of HCV-HCC. As the percentage of poorly differentiated tumor cells is higher in large HCC tumors, 26 the increase in copy number of the other two genes on 8q, MOS and EXT1, may be closely associated with disease progression.…”
Section: Discussionmentioning
confidence: 60%
“…24 The PTK2 gene has also been identified as a target for the amplification event at 8q23-24, and elevated expression of PTK2 is associated with a large tumor size in HCC. 25 Our data revealed that four genes were correlated with poor differentiation of HCV-HCC. As the percentage of poorly differentiated tumor cells is higher in large HCC tumors, 26 the increase in copy number of the other two genes on 8q, MOS and EXT1, may be closely associated with disease progression.…”
Section: Discussionmentioning
confidence: 60%
“…4,13 Other results showed that the oncogenes PTK2 and EIF3S3, mapped to 8q24.3 and 8q23.3, were both upregulated by amplification of this chromosomal region. 25 Our data indicate that telomere shortening plays a causal role in the development of CIN in human HCC. The lack of a further shortening of telomeres above the stage of 5 copies of chromosome 8 indicates that telomeres might have reached a critical short length necessary for cell survival.…”
Section: Discussionmentioning
confidence: 64%
“…4 In particular, chromosome 8q24 amplification has been shown to associate with a number of cancers, including prostate cancer, pancreatic cancer and HCC. [5][6][7][8] In HCC, gain of 8q has been reported to be associated with aggressive tumor behavior and lead to the overexpression of oncogenes. 8,[35][36][37] The loss on 8p was proved to be related to progression and metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In HCC, gain of 8q has been reported to be associated with aggressive tumor behavior and lead to the overexpression of oncogenes. 8,[35][36][37] The loss on 8p was proved to be related to progression and metastasis of HCC. 38 In this study, we have employed QuMA for the determination of relative GPAA1 genomic copy number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation